MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DI SDN BABAKAN TAROGONG 5 BANDUNG PADA PEMBELAJARAN IPS MELALUI STRATEGI PEMBELAJARAN PEMECAHAN MASALAH - Rosilah, Eros Rosilah (Universitas Pendidikan Indonesia, 2016)
Learning Social Studies (IPS) is a compulsory subject taught. Learning IPS has a very wide range of material. Reality on the ground results of test scores of fourth grade students of SDN Babakan Tarogong 5 in social studies subject of natural resources, economic activity and technological advances in the district / city and province is still very low. This is due to social studies learning not meet minimum completeness, because the strategy used so far have not matched the learning process. The purpose of this study to determine the activities of students in participating in learning by using learning strategies of problem solving. The results of this research has reached the average value of the class.Keyword : Natural resources, economic activities, technological progress.